Inklusivisme en eksklusivisme: "n Studie van twee tendense - Venter, Pieter M. (HTS teologiese studies, 2009)
Inclusivism and exclusivism: A study of two trendsThe identity of the church can be either inclusivist or exclusivist. Van Ruler’s theocratic theology views the church as being an inclusive community in service of God’s kingdom. It is the vehicle God uses to introduce his kingdom into the world. According to Van Ruler, however, the church also shows a unique character based on its relationship with Jesus Christ. Although the church can take many forms, Van Ruler’s opinion is that the Christian Church could be advised by Old Testament Israel in this regard. This study shows that both inclusivist and exclusivist trends are present in the Old as well as the New Testament. The New Testament inherited the debate between these two opposing stances from the time of the Second Temple. Returning from exile, Sadocitic priests propagated an exclusivist identity for the Judaeans. Their viewpoint was based on the programme of Ezekiel 40–48, as is illustrated in the literature of Ezra–Nehemiah, the Priestly Writing, Chronicles and Jubilees. On the other hand, indeed there was an inclusivist approach as well, as is depicted in the books of Jonah, Ruth, Trito-Isaiah and even Numbers and Joshua. The conclusion drawn from the study is that both exclusivist and inclusivist trends are present in the Bible. Although the church does not have any other option in the present postmodern world but to be primarily an inclusive community, it should also show some form of exclusivism.